Psychological features of motivational intellect - Hupalovska, V.; Levus, N. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2014)
The features of personality are in-process examined with the different level of motivational intellect. It will be that a personality structure can differently influence on forming of motivation. А person that is characterized the high level of motivational intellect uses all situational possibilities for gaining end, and also building plans, envisages a few variants of decision of problem, taking into account circumstances. By means of method- ologies it is educed on research of motivational and intellectual spheres, that relationships between them are indirect in nature.
Keywords: intellect; motivational intellect; motivation; reason; aim; necessity